Mitochondrial Dysfunction and α-Synuclein Synaptic Pathology in Parkinson's Disease: Who's on First?. (31st March 2015) - Zaltieri, Michela; Longhena, Francesca; Pizzi, Marina; Missale, Cristina; Spano, PierFranco; Bellucci, Arianna
Abstract : Parkinson's disease (PD) is the most common neurodegenerative movement disorder. Its characteristic neuropathological features encompass the loss of dopaminergic neurons of the nigrostriatal system and the presence of Lewy bodies and Lewy neurites. These are intraneuronal and intraneuritic proteinaceous insoluble aggregates whose main constituent is the synaptic protein α -synuclein. Compelling lines of evidence indicate that mitochondrial dysfunction and α -synuclein synaptic deposition may play a primary role in the onset of this disorder. However, it is not yet clear which of these events may come first in the sequel of processes leading to neurodegeneration. Here, we reviewed data supporting either that α -synuclein synaptic deposition precedes and indirectly triggers mitochondrial damage or that mitochondrial deficits lead to neuronal dysfunction and α -synuclein synaptic accumulation. The present overview shows that it is still difficult to establish the exact temporal sequence and contribution of these events to PD.